Combined molecular and periodic DFT analysis of the adsorption of co macrocycles on graphene. Issue 2 (1st November 2017) - Calborean, Adrian; Morari, Cristian; Maldivi, Pascale
Abstract : The molecular doping of graphene with π‐stacked conjugated molecules has been widely studied during the last 10 years, both experimentally or using first‐principle calculations, mainly with strongly acceptor or donor molecules. Macrocyclic metal complexes have been far less studied and their behavior on graphene is less clear‐cut. The present density functional theory study of cobalt porphyrin and phthalocyanine adsorbed on monolayer or bilayer graphene allows to compare the outcomes of two models, either a finite‐sized flake of graphene or an infinite 2D material using periodic calculations. The electronic structures yielded by both models are compared, with a focus on the density of states around the Fermi level. Apart from the crucial choice of calculation conditions, this investigation also shows that unlike strongly donating or accepting organic dopants, these macrocycles do not induce a significant doping of the graphene sheet and that a finite size model of graphene flake may be confidently used for most modeling purposes. © 2017 Wiley Periodicals, Inc. Abstract : This density functional theory study of cobalt porphyrin and phthalocyanine adsorbed on graphene compares the outcomes of two models, either a finite‐size flake or an infinite 2D material. Focusing on the density of states around the Fermi level, this work shows first that a finite model may be able to reproduce the conclusions of the periodic model and that the observed weak doping of graphene with such molecules arises from the symmetric positioning of the gap compared to the Fermi level of graphene.